PENGEMBANGAN MUTU PENDIDIKAN DAN ADAPTASI KEBIASAAN BARU AKIBAT COVID-19 DI SD INPRES PANRANGAJI KABUPATEN BANTAENG - Jainuddin Jainuddin; Abdurrachman Rahim; Andi Irwandi; Nurwidyayanti Nurwidyayanti; A. Rizal A. Rizal (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The Teaching Campus Program which is one form of the implementation of the Merdeka Learning Campus Merdeka (MBKM) in the form of teaching assistance to empower students in helping the learning process in elementary schools in various villages/cities, one of which is SD Inpres Panrangngaji which is located in Campaga Village, Tompobulu District, Bantaeng Regency, South Sulawesi. In this program, students who are involved have a responsibility to help the school in the teaching process, help adapt technology, and assist administration. In addition, students have a responsibility to improve student character and increase student interest in learning during this pandemi. The results of this program are as an inculcation of empathy and social sensitivity in students to the problems of community life around them, honing thinking skills in working together across fields of science and students' diverse origins in solving problems faced by developing students' insight, character and soft skills , encourage and spur national development by fostering community motivation to participate in development, as well as increasing the real role and contribution of universities and students in national development.